â€œAn Analysis of the pattern of household expenditure Indonesian manpower Merubong village Sambas Regency in Malaysiaâ€ - B01112015, Ruslan (Jurnal Pembangunan dan Pemerataan, 2016)
This research aim to describe patterns of expenditure and to examine factors that affect household expenditure of Indonesian migrant worker from Merubong village of Sambas regency working in Malaysia. The data used were primary data collected through questionnaires, direct interviews, while secondary data were obtained from institution related to this research. The sample were 63 respondensts i.e. migrant worker from Merubong village present during data collection.The data collected were analyzed using regression. The dependent variable was expenditure, while the independent variables were wages, and working hours. This research concluded that spending was mostly used to meet basic needs such as food and drink, home improvement, purchase of electronic goods and entertainment. Expenditure for investment such as buying land, saving, and education were of a small amount and incidental. Teh independent variable that affect the expenditure were wages and working hours.Keywords: Remittance, Patterns of Expenditure, Wages, and Working hours.